Necessity to Reconsider Addiction Imaging Policies in Society (Case Study: Karaj City) - habib ahmadi; ali arabi (توسعه اجتماعی, 2016)
Addiction is a wide scope problem with which the cross section of different approaches is ‘prevention’. The first part of the research at hand, takes a qualitative approach and pathological view to investigate drug imaging policies in Karaj city; the second part takes a quantitative approach to test the first part’s result by Social Survey Methods. The required data for this part by researcher made questionnaire were gathered. The findings suggest that current decades’ policies has caused the addiction’s image to be associated with features like homelessness, disorderliness, aimlessness, and unemployment, and addiction to be an issue mostly related to lower classes in society. These findings were confirmed by a social survey, which includes that 80% of the respondents had similar images about addiction in mind. It must be noted that not only this image has failed to increase prevention in young population of Iran, but actually has acted in reverse.